RESPON MASYARAKAT TERHADAP KONDISI PASAR TRADISIONAL DI KECAMATAN TAMPAN KOTA PEKANBARU (Studi Pada Pasar Pagi Arengka) - Irawan, Putra; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Public response towards the condition of traditional market in Tampan district of Pekanbaru city. The study is in Arengka morning market which is located in Soekarno-Hatta street, Pekanbaru. Arengka morning market is the only one market which is open everyday which is located in Tampan district whose the biggest number of population from the another district in Pekanbaru city, with the condition of Arengka morning market includes the merchandise?s price, the safety, the parking, the location of merchandise, and also the quality and the quantity of merchandise in Arengka morning market as the traditional market, and with those conditions how the response of Tampan district?s public as the customers of Arengka morning market.The purpose of this research is to know the Public response towards the condition in that traditional market, as has been described, the respond is physical condition, the parking, quality and quantity of merchandise, etc. the method in this research is quantitative descriptive, which is done in Arengka morning market, with the number of sample is 85 respondents that is found in the location research with accidental technique, and with the respondents? characteristic whose 5 years experience in shopping. In collecting the data, the researcher uses observation technique, leaded interview, and questionnaire.The result research shows that public response which is include the perception, the behaviour, and the participation have showed the positive response. This is because although the condition of the traditional market is not good enough, but only in the specific part, and this is also because Arengka morning market is not managed by government, but managed by private, so those conditions have resemble to the perfection.The Keyword : Public response, Market condition, hope